ปัจจัยที่มีผลต่อการออกไปใช้สิทธิเลือกตั้งระดับท้องถิ่นของประชาชน ตำบลบ้านหว้า อำเภอบางปะอิน จังหวัดพระนครศรีอยุธยา - บานชื่น, อารียา; แสนภูมี, สมชัย (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 2 (2025): วารสาร มมร ยศสุนทรปริทรรศน์-ปีที่ 2 ฉบับที่ 2 (พฤษภาคม-สิงหาคม 2568), 2025)
This research on "Factors Affecting Local Election Participation of Citizens in Ban Wa Subdistrict, Bang Pa-in District, Phra Nakhon Si Ayutthaya Province" aimed to study the factors influencing citizens' decisions to vote in local elections, focusing on personal factors (gender and age), political participation, and access to election information. Data was collected through an online questionnaire (Google Form) from a sample of 316 participants. The findings revealed that gender did not significantly affect the decision to vote in local elections. The Independent t-test results showed that the Sig. value for all gender-related factors was greater than 0.05, indicating no significant statistical difference between males and females in terms of voting decisions. Regarding age, the One-Way ANOVA test results showed that age did significantly influence voting decisions. The Sig. values for several factors, such as election policies (Sig = 0.000), campaign methods (Sig = 0.012), political participation (Sig = 0.000), and voting behavior (Sig = 0.000), were all below 0.05, indicating significant differences between age groups. These findings suggest that election policies, campaign strategies, and political participation have a strong influence on citizens' decisions to vote, particularly when citizens recognize the importance of elections and follow political news. The study recommends the development of election policies and campaign strategies that align with citizens' needs and enhance political participation, especially by raising political awareness among youth and the general public to increase future political engagement.